Superficial Circumflex Iliac Artery-Based Iliac Bone Flap Transfer for Reconstruction of Bony Defects - Yoshimatsu, Hidehiko; Iida, Takuya; Yamamoto, Takumi; Hayashi, Akitatsu (Journal of Reconstructive Microsurgery, 2018)
Background The superficial circumflex iliac artery (SCIA)-based iliac bone flap has yet to be widely used. The purpose of this article is to validate the feasibility of SCIA-based iliac bone flap transfers for reconstruction of small to moderate-sized bony defects. Retrospective outcome comparisons between SCIA-based iliac bone flaps and fibula flaps were made.Methods Twenty-six patients with bony tissue defects underwent reconstructions using either free SCIA-based iliac bone flaps (13) or fibula flaps (13). Outcomes were evaluated 9 months after the reconstruction on the following basis: bone length, pedicle length, skin paddle area, bone union, donor-site complications, skin paddle survival, and complications at the reconstructed site.Results There was no statistically significant difference in pedicle length (iliac bone vs. fibula; 5.5 ± 1.8 vs. 4.1 ± 1.5 cm; p = 0.181), in bone union rate (iliac bone vs. fibula; 100 vs 92.3%; p = 0.308), in donor-site complication rate (iliac bone vs. fibula; 0 vs. 7.7%; p = 0.308), or in skin paddle complete survival rate (iliac bone vs. fibula; 100 vs. 83.3%; p = 0.125). Statistically significant differences were observed in bone flap length (iliac bone vs. fibula; 4.8 ± 2.2 vs. 11.1 ± 4.8 cm; p = 0.0005), in skin paddle area (superficial circumflex iliac artery perforator flap vs. peroneal artery perforator flap; 58.8 ± 35.6 vs. 27.7 ± 17.5 cm2; p = 0.0343), and in reconstructed site complication rate (iliac bone vs. fibula; 0 vs. 30.8%; p = 0.030).Conclusion In our series of SCIA-based iliac bone flap transfers, up to 8 × 3 cm could be procured along the iliac crest. When compared with fibula flap transfers, there were no significant statistical differences in pedicle length or in bone union rate; the SCIA-based iliac bone flap may be a feasible option for bony defects of small to moderate size.
Keywords: superficial circumflex iliac artery; iliac bone flap; osteomyelitis; supermicrosurgery